Analysis of Inflation Management Model Factors as Regards Supply and Demand - Butautas, Dainius (Ekonomika, 2016)
This article analyses the demand and supply aspects of the determinants of CPI inflation in Lithuania in 1998–2008. Content analysis was used to identify and group significant demand and supply inflation factors and using RGT, objectively assess and generalize the results. Pair linear correlation analysis confirmed the significance for CPI inflation of the factors identified through content analysis, and both research methods reliably and effectively helped to identify factors for regression models of inflation. Content analysis revealed that the causes of inflation most often mentioned and traditionally regarded as significant in the economic literature are factors such as money and wages, capital, competition and monopolies, and so on. Pair correlation research showed the significance for inflation of supply and demand factors such as income distribution, income levels, taxes, saving, human capital and labour productivity as well as exports and imports – things which content analysis gave only average or little mention. Regression models confirmed and helped to concretize the significance for inflation of the identified demand and supply factors. The results of the research show that inconsistent monetary and general government expenditure policies reinforce private consumption and capital shocks. Note that human capital and employment, which changed little during the analysed period, did not show the large significance for inflation that they are commonly thought to have.
Keywords: inflation; CPI; demand; supply; human capital; content analysis; Spearman ranks